“Paper Theatre” by Milorad Pavić: mystifications with authorship and masonic symbols - Huk, Zoriana (Respectus Philologicus, 2025)
The article discusses the main poetic aspects of the collection of short stories, Paper Theatre, by the Serbian writer Milorad Pavić. The author of the article examines autobiographical moments and substantiates that Pavić’s work can serve as an illustration of a productive synthesis of fiction and actual events. The dynamic form and implementation of the postmodern concept of the death of the author are considered with the help of multiplicity of authorship, which in turn caused a shift in emphasis to the text and an increase in the status of the reader, who plays a dominant role. Self-citation inherent in postmodernist prose is analysed and realised through the use of already-known fragments, images, heroes, and symbols. Based on the analysis of the stories in the collection Paper Theatre, the elements that echo the Freemasons’ secrets were identified for the first time. This attests to Pavic’s awareness of the ideas of royal art and his desire to “illustrate” Masonic symbolism, which may be the key to reading his works. Particular attention is focused on the story Blue Sweat, where paratextual elements with Masonic signs were discovered. It is concluded that Pavić counted on an exemplary reader who should have the ability to notice the secret symbols of the semantic labyrinth and become the author’s accomplice in intellectual pursuits.